True Knot of Umbilical Cord: A Diagnosis and Prognostic Challenge - Thaís Kappel Vieira Dal Pai (2014)
Introduction: True knot of the umbilical cord is characterized by a cord loop with increased tension and hence higher risk for obstetric and neonatal outcome intervention.